Plan de marketing para la empresa rústicos Finqueros de la ciudad de Loja - Cumbe Valverde, Belen del Rocío (2014)
Companies have a number of drawbacks that hinder their normal development and development, instability of government laws and competitive ability, believe entrepreneurs need to take measures that prevent their companies collapse. This research paper aims to analyze the company rustic landowners of the city of Loja, customers, products, competition and possible ways to increase their sales, to ensure a proper operation, positioning, excellence in service to the customer and thus provide an efficient and effective service. Thanks to the direct observation, interviews and surveys failed to verify that the most feasible for the company to achieve excellence is through the development of a Marketing Plan, because here you will find the more safe and reliable way to identify its main weaknesses, threats, opportunities and strengths. In this way the Manager of the company can make the best decisions always aimed to satisfy the needs of its market and thus to improve its profitability. Resulting in the following proposed goals:  Designing a marketing plan  Stablish an organizational model of the company with the purpose of regulating the jobs within the same design a training  Plan, to the members of the company, and this is to improve the customer service and the work environment.  Develop a plan of promotions, that motivate their clients and would maintain positioning in the market. Through the development of the research on attachment internal analysis process is set to remain in a 72.22% of excellent on the part of the employees towards customers, the 79.51% of clients find what they seek, which implies its variety of products, the 58.33% says the strategic location of the product, which must be improved, with what some strengths of the company are established. Based on the internal analysis instead 96% said that the company does not have a system of offers and promotions of its products, 61% sets that he met the establishment because it transited among in the vicinity of the 74% said not having heard advertising company and 90% said that they make promotions for purchase of products, with laying the weaknesses of the company. In the external analysis is set to 36% and 33 companies like DEKO & roses furniture Iñiguez respectively, as leading companies competitive within the market and the variety of products offered by the company rustic farmers, therefore identifies threats to the company. While that opportunities he determines on the basis that the company rustic farmers remains at 100% quality products, moreover 100% indicates that the company complies with the guarantees of the products offered, the same 100% indicates that the company has low prices in relation to the competition which is consolidated as opportunities for the company that can focus to implement appropriate growth and long term obtain within the local marketprovincial and national. Obtained these proposals was to make their respective conclusions of which stands out the rustic farmers company lacks a plan for job training, situation that affects that workers do not have efficiency in the development of its activities causing a downgrade in the use of production technologies for which it is recommended that the company develop a training plan to technicians and administrative staff to improve its organization and performance in the work area.